Phenotypic plasticity of mate recognition systems prevents sexual interference between two sympatric leaf beetle species. (1st August 2016) - Otte, Tobias; Hilker, Monika; Geiselhardt, Sven
Abstract: Maladaptive sexual interactions among heterospecific individuals (sexual interference) can prevent the coexistence of animal species. Thus, the avoidance of sexual interference by divergence of mate recognition systems is crucial for a stable coexistence in sympatry. Mate recognition systems are thought to be under tight genetic control. However, we demonstrate that mate recognition systems of two closely related sympatric leaf beetle species show a high level of host‐induced phenotypic plasticity. Mate choice in the mustard leaf beetles, Phaedon cochleariae and P. armoraciae, is mediated by cuticular hydrocarbons (CHCs). Divergent host plant use causes a divergence of CHC phenotypes, whereas similar host use leads to their convergence. Consequently, both species exhibit significant behavioral isolation when they feed on alternative host species, but mate randomly when using a common host. Thus, sexual interference between these syntopic leaf beetles is prevented by host‐induced phenotypic plasticity rather than by genotypic divergence of mate recognition systems.